PENGARUH MODEL LATIHAN DENGAN PERMAINAN LEMPAR DAN TANGKAP BOLA TERHADAP PENINGKATAN GERAK DASAR MANIPULATIF ANAK TUNADAKSA SEDANG KELAS V DI SDLB NEGERI KEDUNG KANDANG KOTA MALANG - Tulloh, Luthfi Hidayat; Raharjo, Slamet; Adi, Sapto (Jurnal Sport Science, 2017)
Abstract :The influence of the model of throwing and catching game training on improving the basic manipulative motion of children with disability while in grade V in SDLB N Kedung Kandang Malang, is a study aimed to know the model of game exercises given to the improvement of basic motion of throwing and tank manipulative. This research is a kind of quasi-experimental research using single subject research (SSR) method. To obtain valid results the researcher uses a power test instrument, precision test, endurance test.Keywords :game model, disability, throw and catch